Effect of Natural Pozzolana on Physical and Mechanical Properties of Concrete - Tsion Amsalu Fode; Yusufu Abeid Chande Jande; Thomas Kivevele (Advances in Civil Engineering)
Construction industries are rapidly growing, sacking high amounts of concrete which has a highly dense microstructure with excellent mechanical properties, more durable, and highly eco-friendly materials. Hence, many of the researchers are interested in solving this problem with replacing concrete by natural pozzolana (NP) which is a supplementary cementitious material mostly from volcanic sources having much active silica content that can improve the durability and mechanical properties of concrete. However, it is not well-known which common optimum replacement range can give the most desirable concrete properties. So, the present study sought to review the effects of replacing NP from volcanic sources on the durability, physical, mechanical, and microstructural properties of concrete, also, to identify the most common dose of a positive effect as a replacement in concrete. The review shows that many of NP used by different literature from different places satisfy ASTM replacement standard in concrete, especially, based on its chemical compositions. Also, the review observed that employing NP in concrete significantly improves concrete workability, lengthens setting time, and reduces bulk density, porosity, water absorption, and chloride ion migration by making denser concrete microstructure. In general, adding 5%–20% of NP in concrete significantly improves compressive strength, split tensile strength, and flexural strength. Specifically, most of the studies found 15% replacement of NP having volcanic sources can give optimum strength. Besides these, most of the studies indicated that the improvement of the strength was more visible at the concrete age of 7–28 days.